Biological Effect of Streptococcus pyogenes-Released Extracellular Vesicles on Human Monocytic Cells, Induction of Cytotoxicity, and Inflammatory Response - Murase, Kazunori; Aikawa, Chihiro; Nozawa, Takashi; Nakatake, Ayako; Sakamoto, Kuniyo; Kikuchi, Taisei; Nakagawa, Ichiro (Frontiers in Cellular and Infection Microbiology, 2021)
Most bacteria naturally release spherical lipid-bilayered extracellular vesicles (EVs) containing proteins, nucleic acids, and virulence-related molecules, thus contributing to diverse biological functions including transport of virulence factors. The group A streptococcus, Streptococcus pyogenes (GAS), a major human pathogen, also releases EVs; however, it remains unclear how GAS EVs interact physiologically and pathologically with host cells, and what the differences are between invasive and non-invasive strains. The proteome profile in this study revealed that GAS EVs enclosed many virulence-related proteins such as streptolysin O and NAD-glycohydrolase, facilitating their pathogenicity, and invasive GAS EVs were more abundant than non-invasive counterparts. In terms of biological effects, invasive GAS EVs showed slo-dependent cytotoxic activity and the induction of cytokine expression, contributing to GAS pathogenicity directly. Although non-invasive GAS EVs did not show cytotoxic activity, they may be utilized as a means to prevent antibacterial mechanisms such as autophagy, leading to enhancement of their own survival in the intracellular environment after the infection. These results suggest that invasive and non-invasive GAS EVs play different roles in GAS infection strategy and pathogenicity. Our findings also indicate that EVs could be a key factor for GAS pathogenicity in GAS-host interactions.